Productive Integration of Livestock and Forestry: Impact Assessment in Two Agrarian Clubs in the Department of Durazno, Uruguay - Acosta, Liber; Courdin, Virginia; Arbeletche, Pedro (Agrociencia Uruguay, 2017)
The aim of this study was to evaluate the socioeconomic impact on two agrarian clubs (Agrarian Youth Movement) of a Cooperation Agreement with the forestry company Montes del Plata, within the framework of the Productive Integration Program of the Agrarian Youth Movement in Durazno, Uruguay. The methodological design was qualitative, using the evaluative research as a technique, through impact assessment based on the dimensions of relevance, effectiveness and sustainability. The tools for obtaining the information were the survey and the semi-structured interview with qualified informants and farmers members of both clubs. The analysis of the results showed remarkable differences between the agrarian clubs, mainly due to their distinct conformation, history, working dynamics, productive management of the pasture area in the forest, and their future plans. Among the beneficiary farmers there is a good perception and a positive evaluation of the Program in all dimensions, mainly about the access to the land as a resource, and in the development of different aspects from the group process. The scope and depth of the impact of the agreement in each group are marked by the differences in the group historical process and its strengthening from this enterprise.